Sosialisasi Manfaat Makan Sayur dan Buah Serta Manfaat Olahraga untuk Mencegah Obesitas Pada Lansia di Kecamatan Ubud Kabupaten Gianyar - I Wayan Ambartana; Hertog Nursanyoto (Jurnal Pengabmas Masyarakat Sehat, 2019)
The problem of obesity in the elderly has become a health and nutrition problem in the world community. Obesity does not cause death directly, but causes serious health problems that can lead to cardiovascular, kidney, metabolic, protombic and inflammatory responses. According to WHO (2013) a diet high in energy and fat and lack of movement activity are the main factors causing high rates of obesity throughout the world. Frequent consumption of various types of food that exceeds the need will increase body weight, especially if not accompanied by sufficient body activities such as exercise, obesity will be more easily occur. The results of the 2013 Riskesdas data showed that physical activity lacked the risk of obesity at 1.672 times greater than those who had enough activity. The purpose of this service is to determine the level of understanding the benefits of eating vegetables and fruit and understanding the benefits of physical activity in the elderly. The benefits of socialization are the elderly who understand the benefits of eating vegetables and fruits and the benefits of exercise so they want to consume vegetables and fruits every day and exercise 3 times a week. The target of this service is the elderly. Method: counseling was carried out during the Elderly Posyandu activities. Before counseling, a written Pre-Test / Interview was given. Dedication assisted by several students. After counseling, a post test was conducted. If the elderly are not able to do it themselves, then working on the tets will be guided by the servant.Keywords : Vegetable and Fruit Consumption, Sports Activities, Elderly